Application of a one-dimensional large-strain consolidation model to a full-scale tailings storage facility. (April 2018) - Agapito, Luis Angel; Bareither, Christopher A.
Highlights: Case study of consolidation within a full-scale copper tailings impoundment. Model comparision to measurements of tailings density and impoundment elevation. Tailings density predictions yielded coefficients of determination as high as 0.93. 1-D modeling can yield accurate estimates of density and elevation for design. Abstract: The objective of this study was to evaluate applicability of a commercially-available, one-dimensional (1-D) large-strain consolidation model to predict mine tailings consolidation in a full-scale tailings storage facility (TSF). Data pertaining to tailings production, cyclone operation time, impoundment height, and impoundment volume were made available for a full-scale copper mine TSF. A numerical model was applied to predict tailings consolidation for two considerations: Design Assessment – based on design estimates, and Operation Assessment – based on actual operational data. Comparison between actual average tailings dry density (ρd ) during the first 4 yr of operation and predicted ρd yielded coefficients of determination ( R 2 ) as high as 0.81 for the Operation Assessment and 0.93 for the Design Assessment. Predictions of tailings height for both assessments also agreed well with actual impoundment heights for the first 6 yr of operation. A procedure was developed to predict average ρd of a full-scale TSF that includes (i) estimating TSF volume based on predicted impoundment height and (ii) using TSF volume with dry tailings mass to compute ρd . The main finding was that the modeling of gradual tailings deposition via a 1-D large-strain consolidation model can provide a reliable prediction of tailings height and capacity during TSF operation.